Ankle dorsiflexor muscle size, composition and force with ageing and chronic obstructive pulmonary disease. Issue 8 (9th July 2014) - Maddocks, Matthew; Jones, Matthew; Snell, Thomas; Connolly, Bronwen; de Wolf‐Linder, Susanne; Moxham, John; Rafferty, Gerrard F.
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? The study examined the relationship between muscle size and strength in chronic obstructive pulmonary disease (COPD) patients as well as young and elderly healthy control subjects. We hypothesized that ankle dorsiflexor muscle strength would be reduced by COPD as well as by ageing, and that this would be as a result of changes in both size and composition of the muscle. What is the main finding and its importance? These data demonstrate that the loss of skeletal muscle strength in COPD was related to changes in muscle composition, with infiltration of non‐contractile tissue beyond that seen during normal ageing. Loss of skeletal muscle strength is a well‐recognized feature of ageing and chronic obstructive pulmonary disease (COPD). Reductions in muscle size provide only a partial explanation for this loss of strength, and additional contributory factors remain undetermined. We hypothesized that reductions in skeletal muscle strength, as measured in the ankle dorsiflexor muscles, would be reduced with ageing and COPD as a result of changes in both size and composition of the tibialis anterior muscle. Twenty healthy young subjects, 18 healthy elderly subjects and 17 patients with COPD were studied. Ankle dorsiflexor muscle strength was assessed by maximal voluntary contraction (ADMVC) and 100 Hz supramaximal electrical stimulation of the peroneal nerve (100 HzAD). Tibialis anterior cross‐sectional area (TACSA) and composition, as assessed by echo intensity (TAEI), were measured using ultrasonography. Despite a lack of differences in TACSA between groups, ADMVC and 100 HzAD were significantly reduced in COPD patients compared with both healthy elderly and healthy young subjects, when expressed as absolute values and when normalized to TACSA (P < 0.01). The TAEI was, however, higher in COPD patients compared with healthy elderly (P = 0.025) and healthy young subjects (P = 0.0008), suggesting increased levels of non‐contractile tissue. Across all participants, ADMVC and 100 HzAD correlated positively with TACSA (r = 0.78, P < 0.0001) and negatively with TAEI (r = −0.46, P < 0.0005). The variance in 100 HzAD was best explained with a regression model incorporating TACSA, TAEI, age and COPD status (r2 = 0.822, P = 0.001). These data demonstrate that the loss of skeletal muscle strength in COPD is related to changes in muscle composition, with infiltration of non‐contractile tissue beyond that seen during normal ageing.